KREDIBILITAS KOMUNIKATOR DALAM MENGEMBANGKAN TIM E-SPORT PROFESSIONAL DOTA 2: Studi Analisis Semiotika Film Dokumenter - Alta, Septian Titus Alta Pradana; Yanuar Nurul Fazri; Fajar Nugraha; Ike Junita Triwardhani (Ilmu Komunikasi, FISIP Universitas Pasundan, 2023)
DOTA 2 is one of the E-sports that is officially competed and attracts millions of eyes worldwide. The development of technology can make sports not only in physical form but also in digital form. The purpose of this study is to explain the communication credibility that exists in Ceb regarding the development of the OG eSports team both in game and out game. The research method used is qualitative with a case study approach to the OG eSports Team which won the Stockhold Major 2022 competition. The data analysis technique that the author does by analyzing the semiotics of the documentary film Ceb: The Greatest Comeback of Dota 2. The results of this study found that Ceb has two important factors that must be possessed by a communicator. Ceb has source attractiveness and source credibility factors, these two factors make Ceb very capable of influencing the team to increase motivation and morale. These things cannot be considered easy even though it is only the world of electronic sports, because the pressure in E-sport itself is as high as a conventional sports match usually.